2022
DOI: 10.1002/bio.4345
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric properties of thermoluminescent NaCl pellets from Khewra Salt Mines, Pakistan

Abstract: Thermoluminescence (TL) and extended dosimetric characteristics of naturally occurring sodium chloride (NaCl) salt were studied. Pellets were prepared from mined crystalline salt obtained from Khewra Salt Mines, Pakistan and irradiated from 1 mGy to 10,000 mGy using cobalt-60 gamma source. The TL response showed two dominant peaks around 125 C and 230 C, respectively, at low doses, with an additional peak in between at doses beyond 300 mGy. A linear and supra-linear TL response was observed between 1 mGy-100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…It may also possible that NaCl was formed. The previous study that reported NaCl salts grain morphology was cubic shaped with non-uniform size [23]. The C element was the high composition besides Na and Cl, the C element may be contributed by the amino acid.…”
Section: Resultsmentioning
confidence: 78%
“…It may also possible that NaCl was formed. The previous study that reported NaCl salts grain morphology was cubic shaped with non-uniform size [23]. The C element was the high composition besides Na and Cl, the C element may be contributed by the amino acid.…”
Section: Resultsmentioning
confidence: 78%
“…Notably, graph energy captures the graphical characteristic, while the spectral radius of a graph represents the largest absolute eigenvalue among all the eigenvalues of its adjacency matrix, denoted by the notation ℘(G). Moreover, these mathematical tools have found several applications in algebraic graph theory (Zhang et al, 2022). Both of these tools, i.e., the energy and spectral radius, play pivotal roles in comprehending the structural properties and behavior of graphs across various disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Several minerals have been reported as TL dosimetric material due to their unique TL properties which ultimately depend on the geological processes during formation times [7,[9][10][11][12][13][14][15]. Fluorite (natural CaF2) is only one of them having a Face-Centred Cubic (FCC) structure and is nonhygroscopic in nature.…”
Section: Introductionmentioning
confidence: 99%